Insect pollinator conservation policy innovations: Lessons for lawmakers. Issue 93 (March 2019) - Hall, Damon M.; Steiner, Rebecca
Highlights: We provide a content analysis of 110 subnational insect pollinator policies. We characterize policy trends and document the spectrum of policy innovations. Lawmakers are seeing pollinators as beneficial insects attending to pesticides anew. With a few exceptions, policies are nascent and anemic steps for addressing a crisis. This empirical account anticipates viable international policy and informs its design. Abstract: Global insect pollinator declines are caused by human behaviors of land uses, habitat alteration, pesticides, and others. Policies—as mutually agreed-upon limits to behaviors to achieve shared values—are necessary for addressing complex social-ecological problems like declines of insect pollinator diversity and abundance. Despite scientific calls and public outcry to develop policy that addresses declines, multi-state agreements have not delivered such legislation nor met basic monitoring needs recommended by experts. In the absence of sweeping international agreements targeting pollinator declines, national and sub-national governments are actively deploying policies to address the pollinator health crisis. Although global monitoring and conservation agreements are needed, small-scale policy innovations represent advances in laws. These sub-national actions are effectively piloting new policy instruments in terms that have proven amenable to polarized political parties. To showcase the spectrum of policy innovations, we examine pollinator-relevant polices passed by US state-level legislatures from 2000 to 2017. This timeframe captures pre- and post-publicity of pollinator declines via colony collapse disorder, the evolving research on neonicotinoids, and highly-visible bee kills. We found 109 new laws covering apiculture, pesticides, awareness, habitat, and research. Together, they narrate an evolution of bureaucratic thinking on insects. Yet when compared to policies proposed by biologists, legislators failed to address four of ten policy targets. In politically divided nations, policies that have successfully appealed to and passed laws through sub-national assemblies are predictive of large-scale conservation bills that could win broad support for national laws and international agreements.